1970
DOI: 10.1111/j.1365-2133.1970.tb15736.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Dermangiopathy.

Abstract: SUMMARY Necrobiosis Lipoidica Diabeticorum (NLD) and Pigmented Pretibial Patches (PPP) are characterized by their association with diabetes mellitus, by their pretibial predilection, and by vascular alterations compatible with diabetic microangiopathy. Despite differences in the gross and microscopic morphology, both may be considered part of a spectrum of cutaneous lesions for which the term diabetic dermangiopathy is suggested. Variants within this spectrum are reported, including 2 cases with widespread les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Bauer & Levan (1970) reported two cases of extra-pretibial diabetic dermopathy assoeiated wifh NLD and suggested that diabetic dermopathy may be the precursor of NLD. The hyperpigmented macules of "diabetic dermopathy" sometimes coexist with NLD on the anterior shins.…”
Section: Discussionmentioning
confidence: 99%
“…Bauer & Levan (1970) reported two cases of extra-pretibial diabetic dermopathy assoeiated wifh NLD and suggested that diabetic dermopathy may be the precursor of NLD. The hyperpigmented macules of "diabetic dermopathy" sometimes coexist with NLD on the anterior shins.…”
Section: Discussionmentioning
confidence: 99%
“… 85 The plaques result from the confluence of yellowish papules and often develop atrophic center that corresponds to the dermal and epidermal atrophy associated with superficial telangiectasias. 86 …”
Section: Necrobiosis Lipoidica Diabeticorummentioning
confidence: 99%
“…Although many workers believe that the lesions are significantly related to the occurrence of diabetic macroangiopathic complications (26,54), shin spots may precede the appearance of glucose intolerance {1! 8), and even appear in a small number of individuals who maintain normal glucose tolerance over the subsequent years (118).…”
Section: Diabetic Dermopathymentioning
confidence: 99%
“…It has been suggested that NLD, GA, diabetic dermopathy, and bullosis diabeticorum be classified as diabetic dermangiopathies to emphasize the similarity between the microvascular changes in these four diseases and in the microangiopathic changes in other organ systems observed in diabetic patients (118).…”
Section: Bullosis Diabeticorummentioning
confidence: 99%